The Role of Work-Life Balance on Psychological Well-Being in Employees with Job Satisfaction as a Mediator - Jauharah, Hasna; Zamralita; Fahlevi, Reza (CV. Get Press Indonesia, 2026)
This study examines the role of work-life balance in employees’ psychological well-being, with job satisfaction as a potential mediating variable. Using a quantitative cross-sectional design, data were collected from 284 active employees through convenience sampling using the Work-Life Balance Scale (WLBS), the Psychological Well-Being Scale (PWB-18), and the Job Satisfaction Measurement: the Alternative Method. Data were analyzed using regression and bootstrapping mediation analysis with PROCESS Hayes Model 4. The results indicate that work-life balance has a significant positive effect on psychological well-being. However, work-life balance does not significantly influence job satisfaction, and job satisfaction does not significantly predict psychological well-being; therefore, job satisfaction does not mediate the relationship between work-life balance and psychological well-being. These findings suggest that employees’ psychological well-being is primarily shaped by the direct effect of work-life balance, highlighting the importance of organizational policies that support work-life balance to promote employee well-being.Top of Form